Tensile shear load in resistance spot welding of dissimilar metals: An optimization study using response surface methodology - Sukarman Sukarman; Triyono Triyono; Budi Kristiawan; Amir Amir; Nazar Fazrin; Ade Suhara; Renata Lintang Azizah; Fajar Mucharom (Universitas Muhammadiyah Magelang, 2023)
Resistance spot welding (RSW) is being applied extensively in different industries, specifically the automotive sector. Therefore, this study was conducted to optimize the tensile strength load (TSL) in RSW by investigating the application of dissimilar materials as input parameters. The optimization process involved the combination of different galvanized and non-galvanized steel materials. The production of car bodies using galvanized steel with approximately 13.0 microns thick zinc (Zn) coating was found to be a standard practice, but this zinc layer usually presents challenges due to the poor weldability. This study prepared 27 units of TSL samples using a spot-welding machine and a pressure force system (PFS) for the electrode tip. The aim was to determine the optimal TSL through the exploration of specified RSW parameters. The process focused on using the response surface methodology (RSM) to achieve the desired outcome while the Box-Behnken design was applied to determine the input parameters. The optimal TSL obtained was 5265.15 N by setting the squeeze time to 21.0 cycles at a welding current of 24.5 kA, a welding time of 0.5 s, and a holding time of 15.0 cycles. The highest TSL value recorded was 5937.94 N at 21.0 cycles, 27.0 kA, 0.6 s, and 15.0 cycles respectively. These findings were considered significant to the enhancement of productivity across industries, specifically in the RSW process. However, further study was required to investigate additional response variables such as the changes in hardness and microstructure.